Combination of Moringa Leaf Meal (Moringa oleifera) and Black Soldier Fly Larvae Meal (Hermetia illucens) in Feed to Support Growth Performance in Stiped catfish (Pangasius sp.) Aquaculture - Fahira, Raihan; Dedi Fazriansyah Putra; Gunawan Abdul Wahab; Ismarica; Irwan (Journal of Vocational in Aquaculture (JAVA), 2025)
This study aimed to evaluate the effects of incorporating Moringa leaf flour and maggot flour into feed on the growth performance of stiped catfish (Pangasius sp.). The experiment was conducted using a Completely Randomized Design (CRD) with six treatments and three replications: A (control), B (25% Moringa leaf flour + 5% maggot flour), C (20% Moringa leaf flour + 10% maggot flour), D (15% Moringa leaf flour + 15% maggot flour), E (10% Moringa leaf flour + 20% maggot flour), and F (5% Moringa leaf flour + 25% maggot flour). ANOVA results showed a significant effect (P<0.05) on absolute length and weight gain, feed conversion ratio (FCR), feed efficiency (FE), and specific growth rate (SGR), but no significant effect on survival rate (SR) (P>0.05). Treatment D produced the best growth performance, with an absolute length of 2.06±0.34 cm, absolute weight of 3.91±0.50 g, survival rate of 100.0±0.00%, feed efficiency of 62.34±7.65%, feed conversion ratio of 1.62±0.19, and specific growth rate of 1.69±0.22% per day. Based on the 45-day study, combining 15% Moringa leaf flour and 15% maggot flour in treatment D yielded the best results for stiped catfish growth parameters.